Effect of Reward System on Employee Job Satisfaction The Case Study at Mukono Church of Uganda Hospital - Mary Druscilla Magoola (Uganda Christian University, 2023)
Reward systems are one of the most significant issues of human resource management. Literature from theorists and academics and managers emphasize the types of rewards, intrinsic and extrinsic rewards but additionally, job satisfaction is too well noted. Job satisfaction provides employees with a sense of purpose and belonging to the organization. These feelings make employees fulfill organization goals profitable to the organization; strengthen commitment and loyalty which is necessary in present times where all organizations are looking for competitive advantage. The objective of the research study was to investigate the effect of reward system on employee job satisfaction, a case study on Mukono Church of Uganda hospital. There were three specific goals for the research: to identify the effect of reward system on employee job satisfaction, to examine the effect of organization variables on employee job satisfaction, to determine the relationship between reward system and employee job satisfaction at Mukono Church of Uganda Hospital. The research combined both qualitative and quantitative data collection. The quantitative data was gathered with a specifically created 100 questionnaires and got 92 respondents. Probability sampling was employed to select branches and head office in order to select sample respondent’s simple random sampling was used.This study confirmed that extrinsic and intrinsic rewards are important for employee job satisfaction in the case organization. The study findings indicate that both extrinsic and intrinsic reward variables have effect on the employee job satisfaction. Further research should measure critical factors as behaviors, attitudes, performance and how they are linked to employee job satisfaction. This study contributes to increase in job satisfaction awareness which is important for organizational development.
This is a dissertation